Hydrochemistry and Water Quality of Phoksundo Lake (Dolpa): Insights from the Higher Himalaya Ramsar Site of Nepal - Manyal, Dilendra Singh; Bhattarai, Charan; Paudel, Bal Krishna; Awasthi, Mahesh Prasad; Bohara, Rupesh; Rawal, Sabin; Dhakal, Yubraj; Gaire, Narayan Prasad; Pant, Ramesh Raj (Journal of Institute of Science and Technology, 2025)
Phoksundo Lake, a distinctive 'Y' shaped Ramsar site located in the arid alpine region of the Nepal Himalayas, is a critical freshwater resource with significant ecological and cultural value. This study presents the first comprehensive hydrochemical assessment of the lake to determine its baseline water quality and suitability for drinking and irrigation. Thirteen surface water samples were collected in June 2024 from the lake's inlets, outlet, and main body. Physicochemical analysis revealed that the lake water is of the Ca²⁺-HCO₃⁻ type, with ionic dominance orders of Ca²⁺ > Mg²⁺ > Na⁺ > K⁺ and HCO₃⁻ > SO₄²⁻ > Cl⁻. While most parameters, including electrical conductivity (EC), total dissolved solids (TDS), and major ions, were well within WHO guidelines, the pH (mean 8.88) exceeded the recommended range for potable water. Geochemical modeling using Gibbs and Piper plots confirmed that the lake's chemistry is overwhelmingly controlled by rock weathering, specifically the dissolution of carbonate minerals in the catchment, which explains its natural alkalinity. A weighted arithmetic water quality index (WQI) classified the water as "Excellent" for drinking, yet this was contradicted by the presence of E. coli in several samples, indicating localized anthropogenic contamination. Irrigation suitability indices (SAR, Na%) also rated the water as "Excellent," posing no risk to soil health. This study establishes a crucial hydrochemical baseline, concluding that while Phoksundo Lake remains a pristine, rock-dominated system, emerging microbial contamination necessitates targeted monitoring and management to preserve its ecological integrity. Further investigation across different seasons and depths is recommended for a holistic understanding of the lake's dynamics.